Evaluation of atezolizumab immunogenicity: Clinical pharmacology (part 1) - Benjamin Wu; Nitzan Sternheim; Priya Agarwal; Julia Suchomel; Shweta Vadhavkar; Rene Bruno; Marcus Ballinger; Coen A. Bernaards; Phyllis Chan; Jane Ruppel; Jin Jin; Sandhya Girish; et al. (Wiley, 2022)
Abstract Baseline patient characteristics and prognostic factors are important considerations in oncology when evaluating the impact of immunogenicity on pharmacokinetics (PK) and efficacy. Here, we assessed the impact of anti‐drug antibodies (ADA) on the PK of the immune checkpoint inhibitor atezolizumab (an anti-PD‐L1 monoclonal antibody). We evaluated data from ≈ 4500 patients from 12 clinical trials across different tumor types, treatment settings, and dosing regimens. In our dataset, ~ 30% of patients (range, 13-54%) developed treatment‐emergent ADA, and in vitro neutralizing antibodies (NAb) were seen in ~ 50% of ADA‐positive (+) patients. Pooled time course data showed a trend toward lower atezolizumab exposure in ADA+ patients, which was more pronounced in ADA+/NAb+ patients. However, the atezolizumab concentration distributions overlapped, and drug concentrations exceeded 6 µg/ml, the target concentration required for receptor saturation, in greater than 95% of patients. Patients had sufficient exposure regardless of ADA status. The dose selected to allow for dosing over effects from ADA resulted in a flat exposure‐response relationship. Analysis of study results by ADA titer showed that exposure and overall survival were not affected in a clinically meaningful way. High tumor burden, low albumin, and high CRP at baseline showed the greatest association with ADA development but not with subsequent NAb development. These imbalanced factors at baseline can confound analysis of ADA impact. ADA increases atezolizumab clearance minimally (9%), and its impact on exposure based on the totality of the clinical pharmacology assessment does not appear to be clinically meaningful.